Venomous animals and their venoms. - Bücherl, Wolfgang; Buckley, Eleanor E. (Academic Press, 1971)
Venomous Animals and their Venoms, Volume III: Venomous Invertebrates provides a comprehensive presentation of the entire field of the venomous members of the animal kingdom and chemistry and biochemistry of their venoms, including their pharmacological actions and antigenic properties. This volume focuses on venomous invertebrates, such as insects, centipedes, spiders, scorpions, venomous mollusks, and marine animals. Animals that possess at least one or more venom glands and mechanisms for excretion or extrusion of the venom, as well as apparatus with which to inflict wounds or inject the ve.